Analisis Pemeriksaan Hasil Gambaran Radiografi Os Femur Pada Kasus Fraktur Bagian Proksimal Dengan Menggunakan Anteroposterior (Ap) Dan Lateral - Dewi Febriyanti; Pocut Zairiana Finzia; Sry Syahni Bancin (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze the radiographic examination of the femur in cases of proximal fractures while maintaining patient comfort during the examination at the Radiology Department of the Mother and Child Hospital in Banda Aceh. The research was conducted through direct observation and participation in the radiographic examination process of the femur with proximal fracture cases. The study found that the radiographic examination technique for femur fractures in the proximal region differs from the technique used for femur examinations without fracture indications. To ensure patient comfort during the examination of femur fractures in the proximal region, the femur should not be positioned laterally, as this may increase the patient's pain.